2006
DOI: 10.1007/s00586-006-0154-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomised placebo-controlled trial on the effectiveness of nasal salmon calcitonin in the treatment of lumbar spinal stenosis

Abstract: This is a double blind randomised controlled trial to assess the effectiveness of nasal salmon calcitonin in the treatment of lumbar spinal stenosis. The trial compared the outcome of salmon calcitonin nasal spray to placebo nasal spray in patients with MRI confirmed lumbar spinal stenosis. Lumbar spinal stenosis is one of the commonest conditions encountered by spine surgeons. It more frequently affects elderly patients and lumbar decompression has been used to treat the condition with variable success. Non o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 15 publications
0
26
0
2
Order By: Relevance
“…An old randomized cross-over trial of low methodological quality found a positive effect of intramuscular calcitonin(52), but two more recent studies using intranasal calcitonin could not replicate the findings. (53, 54) In patients with neurogenic claudication and imaging confirmed LSS, the addition of gabapentin to standard therapy (NSAIDs, physical therapy and steel bracing) was superior to placebo both in terms of pain sensory disturbances and walking distance. (55) In subgroup analysis the effect was mainly observed in patients with mild symptoms.…”
Section: Treatment Options (Table 3)mentioning
confidence: 99%
“…An old randomized cross-over trial of low methodological quality found a positive effect of intramuscular calcitonin(52), but two more recent studies using intranasal calcitonin could not replicate the findings. (53, 54) In patients with neurogenic claudication and imaging confirmed LSS, the addition of gabapentin to standard therapy (NSAIDs, physical therapy and steel bracing) was superior to placebo both in terms of pain sensory disturbances and walking distance. (55) In subgroup analysis the effect was mainly observed in patients with mild symptoms.…”
Section: Treatment Options (Table 3)mentioning
confidence: 99%
“…In addition, the definition of radiological LSS varied among studies. Some mentioned dural sac compression 16, while others referred to precise measurement of the lumbar canal 17. Congruence between radiating pain pattern and the radiological level of stenosis was mentioned once.…”
Section: Resutsmentioning
confidence: 99%
“…No serious AEs were reported 111 . In a second randomized controlled trial in lumbar spinal stenosis, a nasal preparation of salmon calcitonin failed to show any significant benefit over placebo in terms of the Oswestry Disability Index score, VAS for leg pain, and walking distance 112 . In patients with degenerative lumbar spinal stenosis (n ¼ 152), methylcobalamin (a form of vitamin B12) 0.5 mg three times daily plus conventional management did not yield any additional improvement in pain or in neurological signs compared with conventional management alone (with the exception of neurogenic claudication, which was significantly improved in the active treatment group) 113 .…”
Section: Other Agentsmentioning
confidence: 98%